Assimilation and intergenerational relations among creative workers: the case of Bengali-Indian immigrants in the Kansas City metropolitan area - Mukherjee, Anirban (Kansas State University, 2012)
This qualitative research explores the relationship between urban amenities and the employment of creative Indian workers using personal interviews conducted with Indian professional workers and their families working and residing in the Kansas City (KC) Metropolitan Area. In addressing the debate of whether creative workers follow jobs or jobs follow creative workers, the findings indicate that the decision of Indian creative workers to locate in the Kansas City metropolitan area was primarily influenced by the availability of job opportunities and had little to do with available amenities. A key finding from this study is that the presence of local amenities central to the lifestyles of American professional workers was more important to Indian professional workers than the availability of ethnic Indian amenities such as Indian grocery stores, restaurants, temples, and the screening of Bollywood movies in local theaters. It was also found that “social” amenities (e.g. participation in ethnic Indian associations and formation of networks with other Indian workers residing in the city) are crucial to the retention of Indian professional workers rather than amenities offered through the market. Further, Indian workers preferred residing in suburbs over inner city neighborhoods because of their strong emphasis on the educational achievement of their children and the presence of better schooling opportunities in the suburbs. While ‘distance from work’ and ‘safety of the neighborhood’ were other amenity considerations shaping the settlement decisions of Indian professionals, the presence of co-ethnics in the neighborhood was not an influential factor. The study revealed that most Bengali professionals considered themselves to be assimilated in United States and they appreciated the fact that they are not forced to forsake any aspects of their ethnic culture in the United States. However, some considered that their hectic work schedule, family responsibilities, and involvement with ethnic Indian associations often inhibit adequate assimilation with Americans outside of work. Furthermore, the research found that most Bengali professionals preferred not to impose career or marital choices on their children. However, most second-generation Bengalis were skeptical of their parents’ overemphasis on academic achievement and interference in their personal lives.
Keywords: Migration; Urban amenities; Indian creative workers; Social networks; Assimilation; Intergenerational relations; Sociology (0626)